Quantification of low concentration elements using soft X-rays at high spatial resolution. Issue 1 (January 2016) - Pinard, P T; Richter, S
Abstract: A review of the remaining challenges in electron probe microanalysis to quantify sub-micrometre features containing elements with a concentration less than 1 wt% is presented. These challenges derive from the equivocal influence of the main experimental parameters (accelerating voltage, beam current, measuring time and X-ray lines) on the achievable spatial resolution and the accuracy and precision of the quantification. This inter-dependence is demonstrated by examples from the literature and from new experimental results. From this survey, five key areas are identified as future research and development topics in order to solve for the discussed challenges and achieve the objective of quantification of low concentration elements using soft X-rays at high spatial resolution.